Exploring Literature Anxiety among Students Studying Literature in English at Universiti Sains Malaysia - Wei, Agnes Lin Liau (2008)
Although there have been efforts to research on anxiety and students' performance in the learning situations, there has not been any recorded research to date on literature anxiety. This study explores the existence of literature anxiety as a new construct in the English Language and Literature Studies section at the School of Humanities, Universiti Sains Malaysia.